The Jurisdictional Approach in Indonesia: Incentives, Actions, and Facilitating Connections - Seymour, Frances J.; Aurora, Leony; Arif, Joko (Frontiers in Forests and Global Change, 2020)
As recently as 2014, the “jurisdictional approach” (JA) was a new, unfamiliar, and contested term among civil society organizations and international donor agencies working on initiatives to reduce deforestation and promote sustainable land use in Indonesia. Understood as a more comprehensive approach to low-emissions development than jurisdictional-scale accounting for REDD+, JA gained steam from challenges faced by early efforts to implement corporate commitments to deforestation-free supply chains. JA initiatives sought to align government-led, multistakeholder processes within provinces and districts with multiple external incentives for jurisdictional-scale performance. By early 2020, elements of the concept had been incorporated into official plans and regulations in several provinces and districts and was recognized in the government’s national medium-term development plan. Over the intervening years, the community of JA proponents and practitioners had grown rapidly, attracted interest from government and corporate officials, and coalesced around a common understanding of what the approach entails. Credible, locally led JA initiatives were underway with international support in at least a dozen provinces and districts, and a national platform had been established to link districts that had committed to sustainability. Those initiatives were accompanied by active discourses on proposals for fiscal transfers and preferential market access to provide incentives for improved jurisdictional-scale performance based on indicators such as reduced deforestation. The potential of JA to generate significant results has been hampered by a number of factors, including: still-limited material incentives for change compared to the factors that drive business as usual deforestation; limited availability of data for better land-use planning; low capacity of district-level officials; and misalignment of government policies between subnational and national entities and across ministries. Assessment of impact is challenged by lag times and confounding variables. In order to adequately test the JA theory of change, greater emphasis on creating external incentives and linking JA initiatives across jurisdictions and scales is needed to complement the facilitation of activities within individual provinces and districts.